HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN TINGKAT PENGETAHUAN IBU TENTANG DAMPAK IMUNISASI DPT DI POLINDES BALONG ANYAR LEKOK - PASURUAN - HARNI, NIKHEN FITRININGTYAS; ERNAWATI, TITIN DWI; MARLINA, NADIA (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACTImmunization is a deliberate attempt to provide immunity to infants / children who are protected from the disease. Knowledge is the result of "knowing" and it happens after people make sense to a particular object. The level of education that is beneficial to the mother in giving immunization to her child, because of normal reactions that arise in children such as fever, fuss, swelling on the side of infection. Therefore, this study was conducted to determine the relationship level of education with pregnant women about the impact of DPT immunization in Polindes Balong Anyar Lekok Pasuruan.This research is an analytic research, with population of all mother under five who is doing DPT immunization at Polindes Balong Anyar Lekok Pasuruan. Samples that took 20 persons using non probability sampling method with accidental sampling technique. The variables in this study are the level of education (independent) and mother's knowledge about the impact of DPT immunization (dependent).Data collection result of the result of questionnaires by respondents then done editing, coding, scoring and tabulating. The results of this study are presented in the form.Based on the result of the research, 20 respondents mostly have enough knowledge about DPT immunization impact as much as 6 respondents (30%) this is due to the low education and mother's knowledge about DPT immunization impact so there are still many mothers who refuse to immunize their baby. It was concluded that most of the respondents had sufficient knowledge about the impact of DPT immunization. This matter contains the effect of age, education, occupation, and information obtained less effective. Sufficient knowledge about the impact of DPT immunization will encourage mothers to make efforts to overcome the impact of DPT immunization. Keywords: Knowledge, Impact, Immunization,